Successful treatment with amoxicillin-clavulanic acid: cutaneous nocardiosis caused by Nocardia brasiliensis - Youqi Ji; Fang Su; Xin Hong; Mengyuan Chen; Yongze Zhu; Dongqing Cheng; Yumei Ge (Taylor & Francis Group, 2023)
Aim To emphasize the role of non-sulfonamides in the treatment of Nocardia infection and reduce the adverse reactions caused by sulfonamides. Methods We retrospectively analyzed a case of cutaneous nocardiosis in an immunocompetent individual. The colonies obtained by staining the pus in the lesion with antacid and culturing the agar plates were identified by flight mass spectrometry. The pathogenic identification showed Nocardia brasiliensis infection and the patient was treated with amoxicillin-clavulanic acid. Results After treatment with amoxicillin and clavulanic acid, the ulcer gradually peeled and crusted, leaving dark pigmentation. The patient has finally recovered. Conclusion: Sulfonamides are the first-line antibacterial agents for years in treatment of nocardiosis but are of great toxicity and side effects. This patient was successfully treated with amoxicillin-clavulanic acid and it provided a reference protocol for patients with sulfonamide-resistant Nocardia or sulfonamides intolerance.